Enhancement of Public and Environmental Health in Tambak Sumur Village, Waru District, Sidoarjo Regency - Abdul Hakim Zakkiy Fasya; Maki Zamzam Zamzam; Atik Qurrota A’yunin Al Isyrofi; Kuuni Ulfah Naila El Muna; Dwi Handayani; A’intan Dwi Dinda Muzdalifah; Lutfiana Fitra Audina; Indah Wahyuni (UNUSA Press, 2025)
This community service program aimed to raise awareness and foster active participation among residents in maintaining environmental health and preventing diseases such as Acute Respiratory Infection (ARI) and dengue fever through an educational-participatory approach. Three primary initiatives were implemented: education on low-smoke waste bins, Black Soldier Fly (BSF) maggot cultivation, and the planting of Family Medicinal Plants (TOGA) and snake plants (Sansevieria trifasciata). The waste bin and TOGA programs demonstrated positive outcomes, including increased knowledge, improved practical skills, and effective utilization of residential yards for self-reliant health and environmental preservation. However, the maggot cultivation program faced challenges, including limited hands-on practice, time constraints, and lack of participant interest, leading to suboptimal results. These findings suggest that program success depends not only on educational efforts but also on individual readiness and social support. Intensive mentorship and more precise participant selection are recommended to enhance program sustainability.